Pharmacotherapy for the treatment of obstructive hypertrophic cardiomyopathy. (22nd January 2020) - Spoladore, R.; Fragasso, G.; Pannone, L.; Slavich, M.; Margonato, A.
ABSTRACT: Introduction : Hypertrophic cardiomyopathy (HCM) is one of the most common genetic heart diseases and represents a leading cause of sudden cardiac death as well as a prevalent cause of heart failure and stroke. HCM is characterized by a very complex pathophysiology, consisting of heterogeneous clinical manifestations and natural history. Left ventricular outflow tract (LVOT) obstruction has been considered the most knowable feature of HCM since the initial clinical descriptions of the disease. Areas covered : In this review, the authors discuss the most recent reports on the pharmacological treatment of obstructive HCM, mainly based on three different levels of intervention: control of symptoms, cardiac metabolism modulation and disease-modifying approaches, including genetic preventive therapies. Expert opinion : There are presently limited data supporting pharmacological interventions for this complex disease. However, an improved understanding of HCM pathophysiology will allow the development of novel treatment options. Two important key messages are to further study drugs with negative but limited previous results and to design new and larger trials for those molecules that have already produced positive results in HCM, especially for pressure gradients and symptoms control.